Promoting the Green Policy for Ease Doing of Business–Investment and Sustainable Development: Lessons Learned From Banyumas Local Government, Central Java Province (Jurnal Bina Praja, 2025)
The sustainable development of business and investment in Indonesia has accelerated the country's economic and social agenda, contributing directly to economic growth and expanding employment opportunities. However, investment policies have not fully addressed the need for sustainable environmental security and health, so the presence of investment often triggers new environmental damage problems. Then, the question is how green policy plays a strategic role in preventing environmental damage in terms of investment and ease of doing business, as well as promoting green policy for green investment. The purpose of this paper is to explore and promote the role and tasks of green policies that take place in many regions in Indonesia so that they can be designed for the media to control land use change for and in the name of encouraging investment and business while still paying attention to and applying the principles of 'green investment,' namely sustainable investment development. With a case study in Banyumas Regency, through a descriptive qualitative data analysis method with a triangulation model of data analysis, the author concludes that green policy in the sustainable development paradigm in the regional and local landscape is not yet in accordance with the principles of 'green policy,' namely development policy (investment and business) that pays attention to and applies sustainable development values, in order to prevent damage to nature, the environment that will threaten the sustainability of development in other sectors. At the local government level, such as in Banyumas Regency, green policies play an important role in preventing environmental damage while also providing direct guidance to potential investors before they undertake further investment activities. Green policies have been proven to provide a comprehensive understanding to potential investors, thus providing a guarantee of investment security. For this reason, green policies should be incorporated into the agenda of ease of doing business and investment. The government as the central regulator, should be brave to promote it to accelerate the agenda of sustainable development.
Keywords: Green Policy; Ease of Doing Business; Investment; Sustainable Development; Banyumas Local Government